Animals in Serbian Poetry of the Second Half of the 20th Century - Avramović, Marko (Poznańskie Studia Slawistyczne, 2021)
During the second half of the twentieth century, unlike some earlier periods, the dominant tendency was to present animals in Serbian poetry in the “mode of new literacy”, i.e. to depict their real existence. This approach began in the middle of the century by Vasko Popa with his famous cycle “List”. After him, numerous Serbian poets continued in that direction. Thus, in his poetry, Aleksandar Ristović, created a lavish bestiary in which he paid the most attention to tiny and seemingly trivial animal species. In his opus, he emphasized the common biological basis and the equal value of humans and animals. However, in the work of the author of the same generation, Borislav Radović, we come across the nostalgia of modern urban man for the animal world. In the generation of poets who affirmed themselves on the Serbian poetry scene during the seventies, one of the important thematic preoccupations was the animal world. From this generation of poets, we pointed out the verses of Petar Cvetković, who presented all the complexity of the animal’s encounter with the human, and Ibrahim Hadžić, who very often humanized the animals he wrote about.